Evolutionary signals of selection on cognition from the great tit genome and methylome. - Laine, V; Gossmann, T; Schachtschneider, K; Garroway, C; Madsen, O; Verhoeven, K; de Jager, V; Megens, H; Warren, W; Minx, P; Crooijmans, R; Corcoran, P; et al. (Nature Publishing Group, 2016)
For over 50 years, the great tit (Parus major) has been a model species for research in evolutionary, ecological and behavioural research; in particular, learning and cognition have been intensively studied. Here, to provide further insight into the molecular mechanisms behind these important traits, we de novo assemble a great tit reference genome and whole-genome re-sequence another 29 individuals from across Europe. We show an overrepresentation of genes related to neuronal functions, learning and cognition in regions under positive selection, as well as increased CpG methylation in these regions. In addition, great tit neuronal non-CpG methylation patterns are very similar to those observed in mammals, suggesting a universal role in neuronal epigenetic regulation which can affect learning-, memory- and experience-induced plasticity. The high-quality great tit genome assembly will play an instrumental role in furthering the integration of ecological, evolutionary, behavioural and genomic approaches in this model species.